2014
DOI: 10.1097/sap.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Vasopressor Use in Free Tissue Transfer for Head, Neck, and Extremity Reconstruction

Abstract: General anesthesia induces hypotension and this is commonly treated intraoperatively with administering vasopressors. Microsurgeons are hesitant to use vasopressors due to the potential risk of inducing vasoconstriction and flap necrosis. The aim of this study was to determine the frequency of intraoperative vasopressor utilization in patients undergoing free tissue transfer reconstruction and to determine its impact on patient outcomes. An IRB-approved retrospective review was performed for 47 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…93 Interestingly, in several clinical studies, intraoperative vasopressor administration affected neither the incidence of flap loss nor the rate of reoperation. [29][30][31][32][33] Cumulative dosage and timing of vasopressor administration showed no correlation with adverse outcomes. 29,33 Dobutamine has been shown to significantly improve flap flow.…”
Section: Vasopressorsmentioning
confidence: 79%
“…93 Interestingly, in several clinical studies, intraoperative vasopressor administration affected neither the incidence of flap loss nor the rate of reoperation. [29][30][31][32][33] Cumulative dosage and timing of vasopressor administration showed no correlation with adverse outcomes. 29,33 Dobutamine has been shown to significantly improve flap flow.…”
Section: Vasopressorsmentioning
confidence: 79%
“…Our PVB groups and ERAS subgroup had similar blood pressure measurements and fluid administration throughout the intraoperative period, and similar doses of vasopressor medications. The use of vasopressors for management of intraoperative hypotension, while previously avoided in microsurgery, has not been found to have a significant adverse effect on flap outcomes, 33 although caution is still recommended based on known effects of vasoconstriction in animal models. 31 , 34 In our study, neither the use of a PVB or our ERAS protocol had an effect on use of vasopressor medications.…”
Section: Discussionmentioning
confidence: 99%
“…These two techniques are easily used in the operating room and their reported sensitivity was up to 60% [48]. Murawa and colleagues [48] published the first use of the SPY system to assess the gastric graft and several other studies [47,49,50] suggested the utility of using this technique. The SPY system may be particularly useful with considerable contribution when a complex esophageal reconstruction is considered to assess the adequacy of supercharged graft blood supply.…”
Section: Intraoperative Assessment Of Conduit Blood Supplymentioning
confidence: 99%
“…Therefore information given by intraoperative assessments can be used to guide intraoperative decision making. As recommended by authors [47,48,49,50], these tools are used in conjunction with clinical acumen to decide whether the conduit blood supply is suitable or whether another conduit must be sought.…”
Section: Intraoperative Assessment Of Conduit Blood Supplymentioning
confidence: 99%